Konsentrasi Perekat Pati Sagu Terhadap Karakteristik Briket Bioarangdari Limbah KulitBuah Durian - Yulia Citra; Farida Hanum Hamzah; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Increasing need of energy and decreasing of fuel supply requires human to discover alternative energy resources. Consequently, there should be a research to discover a new renewable energy source such as durian fruit leather. Durian is biomass that has great potential for bio-briquet. This research aims to discover the precise adhesive consentration rate in sago’s starch , which are 3%, 5%, and 7%. Based on analytical result of durian leather charcoal briquet research, the best quality briquet is the P1 consentration which composed rate are 3%, has 4.04% water content, 19.14% ashes content, 5.502 cal/g heat value, and 0.0017 g/sekoncombustion rate. Keywords: briquet, durian fruit leather, sago starch.